2020
DOI: 10.1016/j.isci.2020.101822
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Inhibitor OPB-51602 Is Cytotoxic to Tumor Cells Through Inhibition of Complex I and ROS Induction

Abstract: Summary STAT3 is a transcription factor involved in several cellular activities including inflammation, proliferation, and survival, but it also plays a non-transcriptional role in modulating mitochondrial metabolism. Given its diverse functions in human cancers, it is an emerging therapeutic target. Here we show that OPB-51602, a small molecule inhibitor of STAT3, is highly toxic in a STAT3-dependent manner. Specifically, drug toxicity depends on mitochondrial STAT3 as tumor cells expressing only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Importantly, the requirement for mitochondrial STAT3 in these processes could be circumvented by modulation of NAD+ levels through supplementation with NAM or restoration of dehydrogenase activity. These results could have therapeutic implications, as it has been shown that targeting NAD+ metabolism can sensitize tumor cells to drug and radiation therapy [85,86], adding another potential rationale for targeting mitochondrial STAT3 during cancer therapy [40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, the requirement for mitochondrial STAT3 in these processes could be circumvented by modulation of NAD+ levels through supplementation with NAM or restoration of dehydrogenase activity. These results could have therapeutic implications, as it has been shown that targeting NAD+ metabolism can sensitize tumor cells to drug and radiation therapy [85,86], adding another potential rationale for targeting mitochondrial STAT3 during cancer therapy [40].…”
Section: Discussionmentioning
confidence: 99%
“…To check this, we augmented NADH dehydrogenase activity in STAT3 KO cells by ectopically expressing yeast NDI1. Yeast NDI1 is a rotenone-resistant and STAT3-independent NADH dehydrogenase that is capable of bypassing defects in complex I function when expressed in mammalian cells [40,55,56]. Interestingly, NDI1 expression restored antioxidant gene expression in STAT3 KO cells to WT levels (Fig.…”
Section: Mitochondrial Stat3 Regulates Expression Of Gsh Biosyntheticmentioning
confidence: 99%
See 2 more Smart Citations
“…Therapies that target tumor cell mitochondria can effectively release the coupling between tumor cells and the “parasitic host,” cutting off the energy source of tumor cells. Mitophagy is correlated with various cancer cell characteristics, including the promotion of ROS production, disrupting the redox balance [ 22 ], accelerating the mitochondrial unfolded protein response (UPRmt), increasing the production of unfolded proteins and toxic metabolites [ 23 ], increasing mitochondrial membrane permeability, promoting cytochrome C release into the cytoplasm to induce cell apoptosis [ 24 ], adjusting intracellular energy metabolism to cause drug resistance [ 25 ], and inducing mitochondrial DNA damage [ 26 ]. Since mitophagy is generally induced in cancer cells, therapeutic strategies targeting mitophagy possess better selectivity and efficiency, which can be a direction for anticancer drug screening.…”
Section: Discussionmentioning
confidence: 99%